Radiation exposure of radiation workers from 1997 – 2006 based on the criteria and working period - toto Trikasjono; Zainul kamal (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2010)
The external acceptance dose of radiation worker inYogyakarta have been studied. This research was done in this three specific areas A,B,C, because of worker in this trihedral have hit high probability radiation exposure. Radiation exposure worker were taken from each worker who wears Thermoluminescent Dosimeteron period 1997-2006. Exposure result of radiation is done every year in Laboratory Safety, Health and Environment, Centre of Research and Development Safety Radiation, National Nuclear Energy Agency. This research aim is to know how much exposure dose of radiation accepted by worker radiation weather have been fulfilled or not the system limitation of dose which have been specified by International Commission on Radiological Protection (ICRP) and or Nuclear Energy Regulation Agency and also determine furthermore step to guarantee health and safety worker radiation worker. Radiation worker that chosen as sample of research are 45 workers that are radiation worker. Data collection which is used in this research using personnel radiation monitors. The result of this analysis indicate that distribution acceptance of annual dose personal of group interval 0-2 mSv, and acceptance of highest dose 6.09 mSv in the year 1998 from section A. Whole acceptance of dose of external personal at worker from third monitored area, still below the dose of limitation Nuclear Energy Regulation Agency which is recommended is 50 mSv/year and ICRP 1990 is 20 mSv/year.Key words: personal radiation exposure, radiation worker, radiation